n-Butyldichlorido (2-{(1E)-1-[2-(pyridin-2-yl) hydrazin-1-ylidene] ethyl} phenolato) tin (IV) - Fasihuddin Badruddin, Ahmad; Md Abu, Affan; Dayang NA, Chee; Seik Weng, Ng; Edward R. T., Tiekink (International Union of Crystallography, 2010)
Two independent molecules comprise the asymmetric unit of the title compound, [Sn(C4H9)(C13H12N3O)Cl2]. The Sn atom in each is coordinated by the tridentate ligand via the phenoxide O, hydrazine N and pyridyl N atoms, forming fiveand six-membered chelate rings. The approximately octahedral coordination geometry is completed by the -C atom of the n-butyl group (which is trans to the hydrazine N atom) and two mutually trans Cl atoms. Differences between the molecules are evident in the relative planarity of the chelate rings and in the conformations of the n-butyl groups [C—C—C—C = 177.2 (5) and 64.4 (11)]. Significant differences in the Sn—Cl bond lengths are related to the formation of N—HCl hydrogen bonds, which link the molecules comprising the asymmetric unit into dimeric aggregates. These are consolidated in the crystal packing by C—HCl contacts. The structure was refined as an inversion twin; the minor twin component is 37 (3)%.